The dual effect of background music on creativity: perspectives of music preference and cognitive interference - Xiao, Xinyao; Tan, Junying; Liu, Xiaolin; Zheng, Maoping (Frontiers in Psychology, 2023)
Music, an influential environmental factor, significantly shapes cognitive processing and everyday experiences, thus rendering its effects on creativity a dynamic topic within the field of cognitive science. However, debates continue about whether music bolsters, obstructs, or exerts a dual influence on individual creativity. Among the points of contention is the impact of contrasting musical emotions — both positive and negative — on creative tasks. In this study, we focused on traditional Chinese music, drawn from a culture known for its 'preference for sadness,' as our selected emotional stimulus and background music. This choice, underrepresented in previous research, was based on its uniqueness. We examined the effects of differing music genres (including vocal and instrumental), each characterized by a distinct emotional valence (positive or negative), on performance in the Alternative Uses Task (AUT). To conduct this study, we utilized an affective arousal paradigm, with a quiet background serving as a neutral control setting. A total of 114 participants were randomly assigned to three distinct groups after completing a music preference questionnaire: instrumental, vocal, and silent. Our findings showed that when compared to a quiet environment, both instrumental and vocal music as background stimuli significantly affected AUT performance. Notably, music with a negative emotional charge bolstered individual originality in creative performance. These results lend support to the dual role of background music in creativity, with instrumental music appearing to enhance creativity through factors such as emotional arousal, cognitive interference, music preference, and psychological restoration. This study challenges conventional understanding that only positive background music boosts creativity and provides empirical validation for the two-path model (positive and negative) of emotional influence on creativity.